Unlawful credit agreement : an analysis of Section 89(5) of the National Credit Act 34 of 2005 with specific focus on Section 89(5)(c) - Van Heerden, C.M. (Corlia) (University of Pretoria, 2015)
Mini Dissertation (LLM)--University of Pretoria, 2014.